SMART HERITAGE POLICY - Bojan Radej; Jelka Pirkovič; Jelka Pirkovič (Innovative Issues and Approaches in Social Sciences, 2018)
European Cultural Heritage Strategy for the 21st Century (Council of Europe, 2017) has importantly contributed to emphasizing integrative intervention logic of heritage policy by shifting from vertical, sector based to cross-sector based horizontal thinking. Paper develops and explain integral logic that combines vertical and horizontal approach. Three integration measures are proposed: weak and strong balance and cohesion. It is illustrated by a hypothetical example showing how integral heritage policy can be programmed (and evaluated) in relatively simple and transparent way, despite its essential complexity.